2016
DOI: 10.1371/journal.pone.0153535
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cutaneous Fatty Acids on the Growth of Pseudogymnoascus destructans, the Etiological Agent of White-Nose Syndrome (WNS)

Abstract: White Nose Syndrome (WNS) greatly increases the over-winter mortality of little brown (Myotis lucifugus), Indiana (Myotis sodalis), northern (Myotis septentrionalis), and tricolored (Perimyotis subflavus) bats. It is caused by a cutaneous infection with the fungus Pseudogymnoascus destructans (Pd). Big brown bats (Eptesicus fuscus) are much more resistant to cutaneous infection with Pd, however. We thus conducted analyses of wing epidermis from hibernating E. fuscus and M. lucifugus to determine their fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Any mechanism to mitigate water loss during hibernation is likely to be advantageous given the pathology of WNS. Recent research even suggests the unique fatty acid composition of E. fuscus wing epidermis may even inhibit fungal growth (Frank et al 2016). In addition, microclimates of hibernacula in the prairies are drier and colder than those of known cave hibernacula (Lausen and Barclay 2006;Klüg-Baerwald unpublished data) and outside the optimal growing conditions of Pd (Langwig et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Any mechanism to mitigate water loss during hibernation is likely to be advantageous given the pathology of WNS. Recent research even suggests the unique fatty acid composition of E. fuscus wing epidermis may even inhibit fungal growth (Frank et al 2016). In addition, microclimates of hibernacula in the prairies are drier and colder than those of known cave hibernacula (Lausen and Barclay 2006;Klüg-Baerwald unpublished data) and outside the optimal growing conditions of Pd (Langwig et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple host traits may contribute to the observed differential impacts of WNS across species (Reeder and Moore 2013;Hayman et al 2016). These traits may include body size, length of hibernation period, attributes of hibernacula and microclimate selection (Wilder et al 2011;Halsall et al 2012;Johnson et al 2014;Grieneisen et al 2015), population size and social structure (Wilder et al 2011;Langwig et al 2012;Frick et al 2015), rates of evaporative water loss (Cryan et al 2010;Willis et al 2011;Warnecke et al 2013), sebaceous lipid composition (Frank et al 2016), and microbial communities on skin surfaces Avena et al 2016). When the fungus does successfully infect the host, immune defences likely affect the outcome of infection (Romani 2011;Johnson et al 2015;Field et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the impact of WNS, a clear understanding of the factors that allow P. destructans to infect its host remain elusive. Studies have suggested several attributes may be important for fungal virulence including the production of small molecule effectors [3], protease secretion [4,5], lipid utilization [6], as well as the fungal heat shock response, cell wall remodeling, and micronutrient acquisition [7]. A significant obstacle to evaluation of these hypotheses has been the lack of a tractable infection model.…”
Section: Introductionmentioning
confidence: 99%